SAT0132 Pain Sensitivity, Disease Activity Assessment and Fibromyalgia Status in Rheumatoid Arthritis. (10th June 2014) - Joharatnam, N.; Mcwilliams, D.F.; Wilson, D.; Wheeler, M.; Pande, I.; Walsh, D.A.
Abstract : Background: Pain remains the most important problem for people with RA. Pain due to non-inflammatory mechanisms can confound the assessment of disease activity. People with established RA may fulfil fibromyalgia classification criteria, which may be associated with a more painful experience. Objectives: We hypothesise that abnormal central pain processing in RA is associated with patient-reported DAS28 components and fibromyalgic features. Methods: Fifty people with stable, longstanding RA recruited from a rheumatology outpatient clinic were recruited. All were using pharmacologic treatments for RA. They were assessed for pain pressure thresholds (PPT) at 3 separate sites (knee, tibia and sternum), 28 joint disease activity score (DAS28) and fibromyalgia classification criteria (Widespread Pain Index and Symptom Severity Scale). Pain (McGill, ICOAP and Likert scale), fatigue (Fatigue Severity Scale), depression (Beck Depression Index II) and anxiety (State-Trait Anxiety Index) were assessed. Multivariable analysis was performed to assess the association between PPT and DAS28 components, DAS28-P (the proportion of DAS28 derived from the patient-reported components of visual analogue score and tender joint count), questionnaires or fibromyalgia status. Results: Median (IQR) age was 60 (54 – 69) and 76% were female, while 21% smoked. Analgesia was taken by 69% (paracetamol 63%, NSAID 16%, opiate 37%). More sensitive PPTs at the medial knee, tibia and sternum were each associated with higher patient-reported DAS28 components (r<-0.45 for all comparisons), higher DAS28-P (r<-0.40), greater reported pain (r<-0.30) and poorer mental health scores (r<-0.12). Multiple regression analysis showed that these associations were not explained by age or gender. A high proportion of participants (48%) satisfied classification criteria for fibromyalgia, which was also associated with more sensitive PPTs at all sites measured, higher patient-reported DAS28 components, higher DAS28-P, greater reported pain and poorer mental health scores. Multiple regression confirmed that fibromyalgia was associated with higher VAS (aOR, 95% CI 3.7, 1.4 – 9.5, p=0.008), independent of other DAS28 components, age and gender. Concurrent RA and fibromyalgia was not associated with any particular biologic or DMARD; nor smoking, age or gender. Neither PPTs nor fibromyalgia were consistently associated with higher inflammatory DAS28 components (higher swollen joint counts or higher acute phase response). Conclusions: People with established RA commonly satisfy fibromyalgia classification criteria, and these people report poorer mental health and display increased pain sensitivity to pressure at non-articular sites. Fibromyalgic symptoms, sensitivity to pain and poorer mental health are all associated with increased DAS28 scores. However, high disease activity scores in some people with RA may reflect augmented pain processing rather than active inflammatory disease. Pain in RA should be managed alongside inflammatory disease activity, as non-inflammatory pain mechanisms are prevalent and suppression of inflammation may not eliminate pain.The contribution of patient reported components to DAS28 should inform decisions on disease modifying or pain management approaches in the treatment of RA. Disclosure of Interest: N. Joharatnam: None declared, D. Mcwilliams Grant/research support: Pfizer UK, D. Wilson: None declared, M. Wheeler: None declared, I. Pande: None declared, D. Walsh Grant/research support: Pfizer UK DOI: 10.1136/annrheumdis-2014-eular.3254